Changes of starch composition by postflowering environmental conditions in kernels of maize hybrids with different endosperm hardness - Martinez, Roberto Dionisio; Cirilo, Alfredo Gabriel; Cerrudo, Anibal Alejandro; Andrade, Fernando Héctor; Reinoso, Luis; Valentinuz, Oscar Rodolfo; Balbi, Celsa Noemí; Izquierdo, Natalia Gabriela (2018)
Starch composition of maize grains is of great importance when used in animal feed and many processing industries. Maize production involves hybrids with different kernel composition and hardness, sown at areas that range from subtropical to temperate cold climates. Therefore, it is relevant to understand how the environment influences starch composition. The objective of this work was to analyze the effect of location and sowing date on starch composition of maize grains.